2019
DOI: 10.15863/tas.2019.10.78.94
|View full text |Cite
|
Sign up to set email alerts
|

Surfaces Quality of Plastic Gears Made by 3d Printing.

Abstract: ISRA (India) = 4.971 ISI (Dubai, UAE) = 0.829 GIF (Australia) = 0.564 JIF = 1.500 SIS (USA) = 0.912 РИНЦ (Russia) = 0.126 ESJI (KZ) = 8.716 SJIF (Morocco) = 5.667 ICV (Poland) = 6.630 PIF (India) = 1.940 IBI (India) = 4.260 OAJI (USA) =

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As a final step, the obtained numerical data (F C (t), ω driver (t), ω driven (t)) were incorporated into Equation (9) and integrated in each time step as follows:…”
Section: Wear Modelling In Gear Pairsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a final step, the obtained numerical data (F C (t), ω driver (t), ω driven (t)) were incorporated into Equation (9) and integrated in each time step as follows:…”
Section: Wear Modelling In Gear Pairsmentioning
confidence: 99%
“…The branch of PLA enhancements is slightly wider if production technologies are considered. Srinivasan et al [8] and Chemezov et al [9] paid much attention to specific production settings, such as printing speed, printing temperature, bed temperature, and infill percentage, in order to enhance PLA's material properties in the case of simple pins and spur gears. Zhang et al [10] performed wear rate tests on a custom-built gear wear test rig to differentiate manufacturing processes in the case of nylon-made spur gears.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that any increase in rotation speed, causes an exponential raise in noise, and pure polyethylene creates much more noise compared to the reinforced gears. Chemzou et al., [ 17 ] produced different filament gears using 3D printing by changing the procedural parameters and studied their effects on mechanical properties. Results showed that lower nozzle velocity allows higher plasticity, surface quality, and gear density.…”
Section: Introductionmentioning
confidence: 99%